Acute management of massive pulmonary embolism in pregnancy - Shahin Qadri; Shahin Qadri; Ashwini Bilagi; Ashwini Bilagi; Abha Sinha; Derek Connolly; Derek Connolly; Derek Connolly; Richard Murrin; Shagaf Bakour; Shagaf Bakour; Shagaf Bakour (Frontiers in Global Women's Health)
Key content•Massive pulmonary embolism (PE) during pregnancy or the postpartum period is a rare but potentially lethal event.•Physiological changes in the coagulation system during pregnancy and puerperium would lead to a hypercoagulable state.•Diagnosis of PE in pregnancy remains a challenge due to physiological changes in pregnancy. There are no validated scoring systems for assessing pregnant/postpartum women with suspected PE. Massive PE should be suspected in all cases with haemodynamic instability in pregnancy.•The Management of massive pulmonary embolism should be timely and aggressive. Thrombolysis for massive PE during pregnancy and the postpartum period has shown to be associated with high maternal and fetal survival (94% and 88%). But other therapeutic options such as (catheter [or surgical] thrombectomy, ECMO) should be considered in the postpartum period, given the high risk of major bleeding with thrombolysis.•Thrombolysis remains the most-used and reasonably successful modality of treatment in pregnancy but should be avoided in the postpartum period as it can cause life-threatening haemorrhage. During the post-partum period, thrombectomy is the treatment of choice.Learning objectives•To understand the pathophysiology of massive PE.•To appreciate the treatment options in pregnancy and postpartum period and their pros and cons.•To understand the need for further work in this area especially in creating a validated algorithm for diagnosing PE in pregnancy and postpartum period.